fahss
fahss
15-07-2019
Mathematics
contestada
[tex]( - 9x + 1) - ( - 7x + 8)[/tex]
Respuesta :
mahamahmood95
mahamahmood95
15-07-2019
Step-by-step explanation:
=(-9x+1+7x-8)
=(-2x-7)
Answer Link
biancaflores2019
biancaflores2019
15-07-2019
Answer:
Step-by-step explanation:
=(-9x+1+7x-8)
=(-2x-7)
Step-by-step explanation:
Answer Link
VER TODAS LAS RESPUESTAS ( 52+ )
Otras preguntas
what are the effects of convection currents in our surroundings?
let A={0,1,2,3,4,6} and B={2,4,6,8} find a.)AnB b.)AUB
use the functions f(x) = 3x – 4 and g(x) = x2 – 2 to answer the following questions. Complete the tables. x f(x)–3–1 0 2
What it is the quadratic formula ?
waht will happen if one of the system fails to carry out its function properly?
Which of Mendel's laws or principles explains that traits are passed from parents to offspring individually instead of as pairs, groups, or sets?A. The Principl
how will you describe the pathway of oxygen in breathing system?
what does it mean to be 'all ears'?
could you tell me what is nonfiction?
what does it mean to be 'all ears'?